A regulamentação da publicidade infantil: implicações sociais para as políticas educacionais - Pelissaro, Karen Girardi (2018)
The present study aims to analyze the challenges posed to Brazilian social and educational policies that focus on the defense and protection of children as opposed to the abusive use of advertising aimed at children consumption. To discuss the theme that evolves the research stand out authors such as Zygmunt Bauman, Yves of LA Taille and Pedrinho Guareschi. Parts of the discussions developed refer to the role of the school as a value-making institution in the face of the massive invasion of children's advertising. Regarding the methodology, this study involves (a) a bibliographical survey, basically consisting of analyzes of books, periodicals, theses and dissertations, (b) documentary research, through Brazilian legislation and legislation in North American countries and (C) the observational method with the video analysis of the channel of the Youtube platform. The result of the work has the azo to corroborate the necessity of having a mechanism with force of law, of in order to make control over this market phenomenon more effective and efficient in Brazil. This is due to the fact that such phenomenon plays a very important role in Brazilian society and, for this reason, interferes in the integral development of children.